(untitled) (Journal of the College of Basic Education, 2026)
The Baha’i religion is considered one of the global religions that received support from certain institutions and countries. Its followers have been known for their peaceful struggle to preserve their faith and follow the teachings of its founder, Baha’u’llah. Despite their peaceful approach, they faced many difficulties and persecution before attaining the position they currently enjoy. The Baha’is in Iraq were not spared from such suffering. Since their early presence in the country, they were subjected to violations, including killings, confiscation of property and temples, and deprivation of their civil rights as a religious minority. Although the number of Baha’is in Iraq is small compared to followers of other religions, their presence deserves documentation and academic attention, especially in light of the marginalization and oppression they endured. The founder of the religion initially attempted to keep the message and beliefs of the faith hidden, as is common with many religions at their inception. Due to the differences in their beliefs from other faiths, the Baha’is faced hostility and rejection from certain religious groups. At times, the Baha’is received support from foreign authorities during their presence in Iraq, but this support did not continue—especially during the Republican and Ba’athist eras, when their suffering intensified. After the American occupation of Iraq, they managed to regain part of their rights, though the earlier violations left a deep impact on their social and religious path.